Sex-based differences in rotational atherectomy and long-term clinical outcomes - Ayoub, Mohamed; Lutsch, Selina; Behnes, Michael; Akın, Muharrem; Schupp, Tobias; Akın, Ibrahim; Rudolph, Volker; Westermann, Dirk; Mashayekhi, Kambis (Journal of Clinical Medicine, 2023)
Present research on the influence of gender on the treatment of coronary artery disease (CAD) and the outcome after percutaneous coronary intervention (PCI) is inconsistent. Sex differences in the presentation of CAD and the success after treatment have been described. We intend to compare the male and female sex in the procedure and the long-term outcome of Rotational Atherectomy (RA). A total of 597 consecutive patients (20.3% female and 79.7% male, mean age 75.3 ± 8.9 years vs. 72.7 ± 9 years, p < 0.001) undergoing Rotational Atherectomy between 2015 and 2020 were enrolled in the analysis. Demographic and clinical data were registered. In-hospital, 1-year, and 3-year MACCEs (major adverse cardiac and cerebrovascular events) were calculated. Women presented more often with myocardial infarction (23.9% vs. 14.9%, p = 0.017). The intervention was mainly performed via femoral access compared to radial access (65.4% vs. 33.6%, p = 0.002). Women had a smaller diameter of the balloon predilatation compared to men (2.8 ± 0.5 mm vs. 3.15 ± 2.4 mm, p < 0.05) and a smaller maximum diameter of the implanted stent (3.5 ± 1.2 mm vs. 4.10 ± 6.5 mm, p = 0.01). In-hospital, 1-year-, and 3-year MACCEs did not differ between the sexes. After a multivariate analysis, no difference between men and women could be detected. In conclusion, this analysis shows differences between women and men in periprocedural characteristics but does not show any differences after RA regarding in-hospital, 1-year-, and 3-year MACCEs.
Veröffentlicht: 31. Juli 2023
Gesehen am 05.10.2023